Evaluation of risk factors in patients attending STI clinic in a tertiary care hospital in North India - Nayyar, Charu (Indian J Sex Transm Dis AIDS, 2015)
BACKGROUND: In the past few years, the interest in STDs and their management has increased tremendously because of their proven role in facilitation of HIV infection, which, in turn, also increases the risk of acquiring STIs. Sexually transmitted diseases (STDs) are a major health problem affecting mostly young people, not only in developing, but also in developed countries Male circumcision is being considered as strategy to reduce the burden of HIV/AIDS. AIMS: (i) To screen the new patients attending the STI clinic for bacterial causes of STIs (Chlamydia trachomatis, Neisseria gonorrhoeae, Treponema pallidum and Gardnerella vaginalis) and (ii) to evaluate the role of various risk factors in the prevalence of STIs. MATERIALS AND METHODS: The present study was conducted on 200 patients attending the STI clinic. They were evaluated for the prevalence of HIV and bacterial STIs (Chlamydia trachomatis, Neisseria gonorrhoeae, Treponema pallidum and Gardnerella vaginalis) along with the role of risk factors particularly circumcision. RESULTS: The prevalence of HIV was 7% and prevalence of other STI was 20%. The causative agents were Chlamydia 8%, Gonorrhea 7.5%, Bacterial Vaginosis 2.7% and Syphilis 2%. CONCLUSION: The factors found to be significantly associated with the prevalence of STI were circumcision, positive HIV status, education, religion, multiple sexual partners, contact with Commercial sex workers (CSW), non use of contraception, profession involving long stay away from home, and past history of STI. The present study suggests that circumcision is a protective factor for acquisition of STIs but other factors like sexual behavior, use of barrier contraceptives, drug abuse etc., also play a role.